Information and design: book symposium on Luciano Floridi's The Logic of Information. Issue 2 (15th January 2020) - Gorichanaz, Tim; Furner, Jonathan; Ma, Lai; Bawden, David; Robinson, Lyn; Dixon, Dominic; Herold, Ken; Søe, Sille Obelitz; Van der Veer Martens, Betsy; Floridi, Luciano
Abstract : Purpose: The purpose of this paper is to review and discuss Luciano Floridi's 2019 book The Logic of Information: A Theory of Philosophy as Conceptual Design, the latest instalment in his philosophy of information (PI) tetralogy, particularly with respect to its implications for library and information studies (LIS). Design/methodology/approach: Nine scholars with research interests in philosophy and LIS read and responded to the book, raising critical and heuristic questions in the spirit of scholarly dialogue. Floridi responded to these questions. Findings: Floridi's PI, including this latest publication, is of interest to LIS scholars, and much insight can be gained by exploring this connection. It seems also that LIS has the potential to contribute to PI's further development in some respects. Research limitations/implications: Floridi's PI work is technical philosophy for which many LIS scholars do not have the training or patience to engage with, yet doing so is rewarding. This suggests a role for translational work between philosophy and LIS. Originality/value: The book symposium format, not yet seen in LIS, provides forum for sustained, multifaceted and generative dialogue around ideas.